ROLEPLAY CHATBOTS AS A POWERFUL LANGUAGE LEARNING TOOL - Mudrynych, Svitlana; Maslova, Larysa; Lysenko, Olena (Sworld-Us Conference proceedings, 2025)
This work examines the efficiency of using of roleplay chatbots, specifically Character AI, as a tool for foreign language learning. It argues that AI-driven chatbots offer significant advantages by creating an interactive and personalized learning enviro